Review studies of Neighborhood Sustainability Assessment tools (Raparin Journal of Humanities (RJH), 2020)
Urbanization due to population growth has negative environmental impact. The sustainable developments of the city and neighborhoods becomes as essential requirement. For this purpose, in the last few years several Neighborhood Sustainability Assessment tools have been developed and used around the world. The aim of this research is comprehensive review of the used neighborhood sustainability assessment tools in the literature and compares the assessment criteria among the tools. The systematical review method is used in this study in order to determine the development, progress, and future direction of this emerging topic. The result of this study shows an overview of neighborhood sustainability assessment tools in the context of annual publications and journal publishers, authors main contribution, published research by countries, common neighborhood sustainability assessment tools in literature, and literature findings. This paper recommends potential research area for future researchers and policymakers of neighborhood and residential sustainable design.